LOS CÉFIROS DEL NACIMIENTO DE VENUS DE BOTICCELLI: UNA HIPÓTESIS - Moya, Francisca (Imafronte, 1997)
In this paper a hypothesis is put foward and argued aboirt the presence and iconography of the so-called «Zephyrs» in Bofficellis Birth of Venus. The author considers that the reading of Poliziano provided Botticelli with !he basis,for the representation of the two figures, one of them being the female wind, which constitutes an innovation in the mythology. justified by the reading and influence of Marsilio Ficino. The pair of figures symbolise the force of love, that equals and creates likenesses, that achieves the exchange of gifs. As in the Spring the pair Zephyri/Cloris-Flora illustrates the change experienced by Zephyr the appears as the loved-one , protecting and bringingflowers, in the Birth however Cloris-Flora is similar to Zephyr; sharing his gift of blowing a soothing wind.